PERAN REGULATOR TERHADAP STANDAR AKUNTANSI KEUANGAN (SAK) SAAT PANDEMI COVID-19 di INDONESIA - John Fery Sonoto (KRISNA: Kumpulan Riset Akuntansi, 2021)
A business entity should consider going concern in preparing its financial statements if there are events that are significant after the reporting period that could threaten the going concern of the business in the future. Entities should use their judgment on whether the Covid-19 pandemic may affect the entity's business continuity taking into account all relevant facts and information. The Financial Services Authority (OJK) together with the Indonesian Institute of Accountants (IAI) as the authorized institution to provide a positive signal for the continuity of the entity's business, through adjustments to PSAK 68 concerning the measurement of fair value of securities and PSAK 71 concerning calculation of reserves. This article proves that the government, in this case the OJK and IAI, has the authority to choose the accounting standards to apply.